Situation Analytics and Model-based User Interface Development: A Synergetic Approach for Building Runtime-Adaptive Business Applications - Christian Märtin; Felix Kampfer; Christian Herdin; Lionnelle Biawan Yameni (Complex Systems Informatics and Modeling Quarterly)
Situation analytics can be used to recognize the changing behavior, emotional state, cognitive load and environmental context of a user during complex task processing. This article discusses the SitAdapt 2.0 architecture that combines a situation analytics platform with pattern- and model-based user interface construction tools in order to build runtime-adaptive interactive business applications with enhanced user experience and task-accomplishment characteristics. The article focuses on the software components and tools for observing and tracking the user, data types for modeling situations, recognizing situations, and modeling structural changes and actions for generating the dynamic adaptations. The situation recognition capabilities and adaptive functionality of the system are demonstrated for web-applications for long-distance travel booking and a beauty products web-portal.